MASUK ANGIN DALAM BUDAYA JAWA - , Atik Triratnawati, Dra.,MA., Dr. Ida Rochani Adi, S.U. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Among the Javanese, the term masuk angin is more frequenty heard than other illnesses. The population who suffers from masuk angin are not only of a certain sex, age, socioeconomic status, or geographical location. Masuk angin affects not only oneâs physical, but also mental. The research aimed to find out the Javanese concept and philosophy of masuk angin as a cultural phenomena: its cause and symptom, how to manage masuk angin based on the Javanese experience, to treat it and the tools use, and also the tratment of masuk angin from the medical point of view. An ethnographic study was carried out among the Javanese peasants in Sleman and fishermen in Rembang, Central Java, from 2007-2010. Participation observation and in-depth interviews were conducted among 68 informants and 25 key informants. The combination of phenomenology, structuralism and symbol theories were applied to analyze and interprete the research data. The Javanese believe masuk angin as natural heath problem due to the fact that it is the effect of too much air entering the body, thus the equilibrium of the body is distrubed. The physcal symptoms of masuk angin incuded headache, fever, chills, feeling restless, bloated stomach, achy joint, etc. Fatigue, the rain, cold condition of the body due to delayed eating, sleeping in the open air, lack of sleep, mental stress, and work hard were said to be among the causes of masuk angin. The coining is usually selected as a first treatment for masuk angin, besides jamu, massage, soda water and hot water to release the gas from the body. The phylosophy of the treatment is a binary opposition and to make equilibrium in the body not only the physical, mental, but also social. The Javanese cosmology such as manunggaing kawula Gusti (unity to the God), and sangkan paraning dumadi (realized about human life) become the life goal, in order safety, health, distance from unfortunated